Analisis Kualitas Aplikasi E-Court Menggunakan Model ISO/IEC 25010:2011 (Studi Kasus Pengadilan Agama Bekasi) - Baros, Cuzaintra; Supono, Riza Adrianti (UNIB Press, 2025)
E-Court is a system designed to digitize and accelerate the process of case administration and trials in court. Given the importance of the quality of this application to support the performance of judicial administration, a comprehensive evaluation of various aspects of quality is crucial. This study aims to assess the quality level of the E-Court application used in the Bekasi Religious Court based on the ISO/IEC 25010:2011 standard with eight characteristics, namely: functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. The study was conducted by collecting data by distributing questionnaires to service users, and the results of the study showed that the quality of the e-court application in the Bekasi Religious Court was considered Very Good, making the E-Court application in the Bekasi Religious Court easy to use and accessible to all levels of society. This study concludes that the E-Court application at the Bekasi Religious Court has met most of the quality criteria according to ISO/IEC 25010:2011, with the highest percentage obtained in the compatibility indicator with a value of 89%, followed by portability 88%, functional suitability 87%, security 87%, maintainability 87%, usability 85%, and performance efficiency 84%. The indicator with the lowest percentage is reliability, which is 83%. Keywords: E-Court Application, ISO/IEC 25010:2011 Method, Bekasi Religious Court